Long COVID-19/post-COVID condition in children: do we all speak the same language? - Silvia Garazzino; Marco Denina; Giulia Pruccoli; Elisa Funiciello; Ugo Ramenghi; Franca Fagioli (BMC, 2023)
Abstract Post-COVID condition is a new and highly debated entity that is still to be outlined in its complexity, especially in the pediatric population. In response to the article by Trapani and colleagues, we report the results of a long-term follow-up conducted in the outpatient clinic of the Pediatric Infectious Diseases Unit on children admitted to our hospital with SARS-CoV-2 infection.